Peran Kepala Sekolah/Madrasah Dalam Menjaga Mutu Pendidikan Pada Masa Tersebarnya Virus Corona (Covid-19) - Hanafiah, Muhammad Ali (Al-Fikru: Jurnal Ilmiah, 2021)
The school principal is the spearhead of an educational institution, Forward and withdrawal of an educational institution on the quality of education depends on the principal in managing it. The challenges of the digital era education era 4.0 can be implemented if educational institutions are supported by the government in the implementation process. The worldwide corona virus and its impact on our education process is a lesson for all of us so that we can change the education process to be even better and be able to compete with other countries.